Assessment of Arterial Stiffness by Cardio-Ankle Vascular Index for Prediction of Five-Year Cardiovascular Events After Coronary Artery Bypass Surgery - Alexei N. Sumin; Anna V. Shcheglova; Irina I. ZHidkova; Sergey V. Ivanov; Olga L. Barbarash (Ubiquity Press, 2021)
The study aim was to investigate the possibility of cardiovascular complications development predicting during a five-year follow-up of patients after coronary artery bypass grafting (CABG) using the cardio-ankle vascular index (CAVI) assessment. Methods: Three hundred and fifty-six patients after elective CABG were enrolled in the study. Prior to surgery, arterial stiffness was assessed in all patients using CAVI. The follow-up was performed five years after the surgery, information was obtained on 238 patients, who were divided into two groups: patients with pathological (≥9.0, n = 88), and normal (<9.0, n = 150) CAVI. Results: Pathological CAVI (≥9.0) was detected in 33% patients before CABG, in stepwise analyses only age and left atrium dimensions statistically significantly predicted CAVI. In patients with pathological CAVI the combined endpoint (major adverse cardiovascular events and hospitalization) and cardiovascular death developed more often in a five-year follow-up after CABG compared with normal CAVI (48.86% versus 34.9%, p = 0.034 and 4.55% versus 0.67%, p = 0.049, respectively). Pathological CAVI (p = 0.021) and the number of coronary bypass grafts (p = 0.023) were independent factors associated with the combined endpoint. Conclusions: Patients with pathological CAVI before CABG surgery are more likely to develop cardiovascular complications and cardiovascular death within a subsequent five-year follow-up. Evaluation of CAVI after CABG in dynamics deserves further study, it is important for monitoring the effects of secondary prevention and the possibility of influencing the prognosis.